A Community Based Study of Feeding & Weaning Practices in Under Five Children in Semi Urban Community of Gujarat - Bhanderi, Dinesh; Choudhary, Sushilkumar (National Journal of Community Medicine, 2011)
The practices of breast feeding & weaning prevailing in the community play a crucial role in deciding the health of a child. The present community based cross sectional study was conducted to study the attitudes, beliefs and behavior regarding feeding and weaning practices; and the influence of various epidemiological factors on these practices in children of 0-5 years of age group. We selected 300 children of age group 0-5 years by using systematic sampling method from randomly selected three wards of Petlad town. The data collected, was subjected to simple proportions and c2 test. Our study suggests that the feeding & weaning practices in the under five children are strongly influenced by factors like mother’s education, provision of antenatal care, place of delivery & prevailing sociocultural beliefs but not by socioeconomic status. In addition, these practices do affect the growth parameters of a child.